2009
DOI: 10.1007/s10916-008-9251-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Informal Health Payments: The Example from Turkey

Abstract: Little is known about the factors that can affect informal health payments in Turkey, which is pertinent given that Turkey has been undergoing and considering a series of reforms in the health sector. This paper aims to examine the predictors of informal payments in Turkey. The study surveyed a random sample of 3,727 people in a medium-sized city, of whom 706 received medical care for illness and/or non-illness related reasons, using a Turkey-specific version of a model questionnaire focused exclusively on inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 21 publications
8
53
0
Order By: Relevance
“…Some studies have reported a meaningful relationship between informal payment behavior with gender, age, educational level, place of residence, health insurance coverage and household economic status (6,13,22,(38)(39)(40)(41)(42). This discrepancy in the results can be attributed to the study setting (hospi- tal or household), the type of surveyed patients, country of study, and the data analysis methods.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a meaningful relationship between informal payment behavior with gender, age, educational level, place of residence, health insurance coverage and household economic status (6,13,22,(38)(39)(40)(41)(42). This discrepancy in the results can be attributed to the study setting (hospi- tal or household), the type of surveyed patients, country of study, and the data analysis methods.…”
Section: Discussionmentioning
confidence: 99%
“…Informal payment is a part of out of pocket payments and it is a distinctive feature of health systems in many countries around the world [5]. Such a payment is a source of inequity and inefficiency in a health system [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of data on informal patient payments is universally recognized, there have been few attempts to study this phenomenon, especially in the context of Iran (1,18). This might be due to the challenges involved in data collection, given the informal and potentially sensitive nature of the topic (3,19,20). To fill this knowledge gap, this paper aimed to identify the motivations behind informal payments in Iran, how informal payments are perceived and why they are made in the health system of Iran from the perspectives of patients, health care providers and officials.…”
Section: Introductionmentioning
confidence: 99%